Moving on: Is Existenzminimum Still Relevant? - Marchand, Bruno (2019)
In the inter-war period, progressive architects confronted the building of mass housing with an analogy with rational and functional workplaces. At the 2nd CIAM (Congrès Internationaux d’Architecture Moderne), held in Frankfurt in 1929, this was tested against the formulation of space standards for a vital minimum, in order to increase the quantity of housing and reduce construction costs. This approach presumed the search for optimal living conditions and hygiene. The analogy with the world of work is particularly striking in the case of design of kitchens, removable furniture and storage spaces to maximize the use of space. In rational—and above all minimum—housing, the size of the rooms mainly depends on the size of the furniture. In this perspective, today in Switzerland new housing projects face the same issues, caused by a housing shortage that has plagued the country in the last decades. This suggests that Existenzminimum is still current for contemporary design.